St. Vincent [videorecording (DVD)] - Melfi, Theodore; Murray, Bill, 1950 September 21-; McCarthy, Melissa, 1969-; Watts, Naomi, 1968-; O'Dowd, Chris, 1980-; Howard, Terrence
Maggie, a single mother, moves into a new home in Brooklyn with her twelve-year old son, Oliver. Forced to work long hours, she has no choice but to leave Oliver in the care of their new neighbor, Vincent, a retired curmudgeon with a desire for alcohol and gambling. An odd friendship soon blossoms between the improbable pair. Together with a pregnant stripper, named Daka, Vincent brings Oliver along on all the stops that make up his daily routine, race track, strip club, and a dive bar.